Differences in ergonomic and workstation factors between computer office workers with and without reported musculoskeletal pain. - Sant'Ana Rodrigues, Mirela; Veraldi Leite, Raquel Descie; Maira Lelis, Cheila; Chaves, Thaís Cristina (Work, 2017)
BACKGROUND: Some studies have suggested a causal relationship between computer work and the development of musculoskeletal disorders. However, studies considering the use of specific tools to assess workplace ergonomics and psychosocial factors in computer office workers with and without reported musculoskeletal pain are scarce. OBJECTIVE: The aim of this study was to compare the ergonomic, physical, and psychosocial factors in computer office workers with and without reported musculoskeletal pain (MSP). METHODS: Thirty-five computer office workers (aged 18-55 years) participated in the study. The following evaluations were completed: Rapid Upper Limb Assessment (RULA), Rapid Office Strain Assessment (ROSA), and Maastricht Upper Extremity Questionnaire revised Brazilian Portuguese version (MUEQ-Br revised). Student t-tests were used to make comparisons between groups. RESULTS: The computer office workers were divided into two groups: workers with reported MSP (WMSP, n = 17) and workers without positive report (WOMSP, n = 18). Those in the WMSP group showed significantly greater mean values in the total ROSA score (WMSP: 6.71 [CI 95%:6.20-7.21] and WOMSP: 5.88 [CI 95%:5.37-6.39], p = 0.01). The WMSP group also showed higher scores in the chair section of the ROSA, workstation of MUEQ-Br revised, and in the upper limb RULA score. The chair height and armrest sections from ROSA showed the higher mean values in workers WMSP compared to workers WOMSP. A positive moderate correlation was observed between ROSA and RULA total scores (R = 0.63, p < 0.001). CONCLUSION: Our results demonstrated that computer office workers who reported MSP had worse ergonomics indexes for chair workstation and worse physical risk related to upper limb (RULA upper limb section) than workers without pain. However, there were no observed differences in workers with and without MSP regarding work-related psychosocial factors. The results suggest that inadequate workstation conditions, specifically the chair height, arm and back rest, are linked to improper upper limb postures and that these factors are contributing to MSP in computer office workers.